Pengaruh Work Family Conflict Dan Beban Kerja Terhadap Kinerja Karyawan Wanita Dengan Stres Kerja Sebagai Variabel Intervening - Muhareni, Iin; Rusdi, Muhammad; Shalihah, Bunga Mar'atush (Al Huwiyah: Journal of Woman and Children Studies, 2022)
This study aims to determine and analyze the effect of work family conflict and workload on the performance of female employees at Bank Sumsel Babel Syari'ah with work stress as an intervening variable. The sample in this study were female employees who worked at Bank Sumsel Babel Syariah who were married and had children, totaling 35 people. The results showed that work family conflict had no effect on the performance of female employees of Bank Sumsel Babel Syariah. However, workload has a positive and significant effect on the performance of female employees of Bank Sumsel Babel Syariah. Then work stress has a negative and significant effect on the performance of female employees of Bank Sumsel Babel and work family conflict has a positive and significant effect on stress. Workload has a positive and significant effect on work stress on female employees of Bank Sumsel Babel Syariah. Based on the results of the analysis of work stress is not able to mediate the effect of work family conflict on employee performance. Then based on the results of the analysis using the causal step method, job stress is able to mediate the effect of workload on employee performance